Syringomyelia in three small breed dogs secondary to Chiari-like malformation: clinical and diagnostic findings - Park, Chul (The Korean Society of Veterinary Science, 2009)
Three small breed dogs were referred for the evaluation of neurologic deficits. Upon physical and neurologic examination, all dogs displayed hyperesthesia, pain, and neck stiffness. Magnetic resonance imaging was performed on the brain and spinal cord, and all three dogs presented Chiari-like malformations and syringomyelia. These dogs were treated with prednisolone and furosemide, and showed rapid improvement of clinical signs. Chiari malformations and syringomyelia were not improved because of congenital disorders. This case report demonstrates the clinical and diagnostic features of Chiari-like malformations and syringomyelia in three small breed dogs.